Um estudo da tradução de Primeiras estórias para o inglês - Liporaci, Vanessa Chiconeli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The main objective of the present dissertation is to analyze the relation between Primeiras estórias, by Guimarães Rosa and its translation into English entitled The third bank of the river and other stories, by Barbara Shelby. In order to do so, we have analyzed four narratives from Rosa's book - A terceira margem do rio, A menina de lá, A benfazeja and Partida do audaz navegante - and their respective translations into English. We started with the selection and study of three types of sentences, which, from what we could see, consist of one of the main characteristics of Rosa's poetic production and were carefully created in order to veil the metaphysic-religious theme that is so important in his books. In addition, we looked for the author's ideas of translation and literary production in the letters that he exchanged with his translators - Edoardo Bizzarri, Curt Meyer-Clason and Harriet de Onís - in order to have his own impressions of this subject, which contributed greatly to the analyses conducted. We noticed that these textual components - the sentences - are strategically inserted in key-points of the narratives and, if modified or omitted in the translation, can spoil the construction of the deepest meanings of these short-stories. Moreover, we carried out a study of the relationship between author, translator and editor, based on some correspondence we found at the Harry Ransom Center, in Austin - Texas. The analysis of these letters also enabled us to access other aspects, which may have influenced the translation process

O objetivo principal do presente trabalho é analisar a relação entre Primeiras estórias, de Guimarães Rosa e sua tradução para o inglês intitulada The third bank of the river and other stories, de Barbara Shelby. Para tanto, realizamos as análises de quatro narrativas dessa obra - A terceira margem do rio, A menina de lá, A benfazeja e Partida do audaz navegante - e de suas respectivas traduções para o inglês, partindo do levantamento e estudo de três tipos de frases que, a nosso ver, consistem em uma das principais características do fazer poético rosiano e foram cuidadosamente trabalhadas no intuito de revestir a temática metafísico-religiosa tão cara à obra desse autor. Além dessas nossas sugestões, buscamos, na correspondência que Guimarães Rosa trocou com seus tradutores - Edoardo Bizzarri, Curt Meyer-Clason e Harriet de Onís - posições rosianas quanto ao fazer tradutório e literário que, compondo uma espécie de poética rosiana da tradução, também contribuíram para as análises efetivadas. Constatamos que esses componentes textuais - as frases - são estrategicamente inseridos em momentos-chave das narrativas e, se modificados ou omitidos na tradução, podem vir a prejudicar a construção dos sentidos mais profundos desses contos. Ademais, fizemos um estudo das relações entre autor, tradutor e editor a partir da correspondência que encontramos no Harry Ransom Center, localizado em Austin - Texas. A análise dessas cartas também permitiu que tivéssemos acesso a outros aspectos que podem ter influenciado o processo de tradução
A study of the translation of Primeiras estórias into English
Keywords: Rosa, João Guimarães 1908-1967 Primeiras estórias; Literatura brasileira; Prosa brasileira; Contos brasileiros; Tradução e interpretação; Brazilian literature